HUBUNGAN PENGUASAAN MUFRADAT DAN TINGKAT PEMAHAMAN MEMBACA TEKS ASLI BAHASA ARAB MAHASISWA - Baso, Yusring Sanusi; Rahman, Faridah; Haeruddin, Haeruddin; Safa, Najmuddin Abd (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2016)
This research studied the relationship between vocabulary mastery and the level of comprehension in reading Arabic authentic text. This research investigated students' lexical threshold to measure the level of comprehension on Arabic authentic text. The data were collected from 47 participants at Arabic literature department of Hasanuddin University. Three test instruments were given, they are Reading Comprehension Test (RCT) that students were asked to sign unknown word meaning in Arabic texts, answer the questions from texts given, and work on Lexical Coverage Test (LCT) to get accurate word list of unknown vocabularies. The result was obtained through applying regression and it showed that the level of reading comprehension was affected 68% by vocabulary mastery. Also, there were 32% of the students depend on the topic or variables out of the variable of vocabulary that was not measured in this research.DOI: 10.24865/ajas.v1i2.12